2021
DOI: 10.1001/jamanetworkopen.2021.36823
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Sex and Immune Checkpoint Inhibitor Outcomes for Patients With Melanoma

Abstract: Key Points Question Does the effectiveness of cancer immunotherapy vary between female and male patients with advanced melanoma? Findings In this population-based cohort study that included 1369 patients 65 years of age or older with advanced melanoma, a significant sex difference in overall mortality was seen among patients treated with nivolumab plus ipilimumab combination immunotherapy, with women having a 2-fold higher mortality risk than their male cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 32 publications
2
24
1
Order By: Relevance
“…Our study found that gender is not associated with the efficacy of immunotherapy for lung cancer. This is different from the results of previous studies ( Jang et al, 2021 ; Wu et al, 2018b ). We found that the reason for the different results among the studies may be due to different patient populations.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our study found that gender is not associated with the efficacy of immunotherapy for lung cancer. This is different from the results of previous studies ( Jang et al, 2021 ; Wu et al, 2018b ). We found that the reason for the different results among the studies may be due to different patient populations.…”
Section: Discussioncontrasting
confidence: 99%
“…We found that the reason for the different results among the studies may be due to different patient populations. The study by Jang et al (2021) included patients with melanoma; Wu et al (2018b) included patients with various tumor types, while our study just included patients with lung cancer. The efficacy of immunotherapy varies by tumor types.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, we analyzed the baseline characteristics of study participants, such as sex and age as these biological variables were demonstrated to affect the immune system and correlate with the ICI therapy efficacy. For instance, several studies reported that males benefited more from ICI therapy than females [39][40][41]. However, it was indicated that the effect of sex difference was more obvious in patients treated with the CTLA-4 inhibitors administered as mono-or combination therapy than the PD-1 inhibitors alone.…”
Section: Discussionmentioning
confidence: 99%
“… 10 Altogether, this may explain why ICIs become less effectual. 11 Since evidence suggests that men and women respond differently to therapies, it is important to explore these differences to redefine clinical decision making and improve outcomes for all patients with cancer. A first step of that discovery is through an examination of the current evidence.…”
Section: Introductionmentioning
confidence: 99%
“…Another study discovered that in female antigens are not as frequently presented to the immune system by the major histocompatibility complex 10. Altogether, this may explain why ICIs become less effectual 11. Since evidence suggests that men and women respond differently to therapies, it is important to explore these differences to redefine clinical decision making and improve outcomes for all patients with cancer.…”
Section: Introductionmentioning
confidence: 99%